Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Materi Menulis Puisi Bebas melalui Penggunaan Model Pembelajaran Picture and Picture pada Siswa Kelas XI TKJ-1 SMK Negeri 2 Karang Baru Kabupaten Aceh Tamiang - Ash Habibi (Medan Resource Center, 2022)
The objectives of this study are: To Improve Learning Outcomes Indonesian Free Poetry Writing Material for Class XI TKJ-1 Students of SMK Negeri 2 Karang Baru Aceh Tamiang Regency Through the Use of Picture and Picture Learning Models. This study used action research as many as two cycles of 4 meetings. Every te cycle. From the results of analysts, it was found that student learning achievement increased, namely cycle I of the first meeting (60%), the second meeting (65%), and cycle II of the first meeting (80%), the second meeting (90%). from this research are: (1)